2020
DOI: 10.1186/s40360-020-00430-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral intermittent vitamin D substitution: influence of pharmaceutical form and dosage frequency on medication adherence: a randomized clinical trial

Abstract: Background: To assess adherence to and preference for vitamin D substitution with different pharmaceutical forms and frequencies of administration. Methods: A focus group of stakeholders aimed at preparing the design of an interventional, randomized, crossover study with 2 × 2 groups obtaining monthly or weekly vitamin D products in liquid or solid form for 3 months each. Dosage corresponds to cumulated amount of recommended 800 IU daily (5.600 IU weekly / 24.000 IU monthly). Main inclusion criteria were a vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In both groups, a majority of the patients achieved sufficient 25(OH)D values, and only 12% reached the optimal range. This result is in line with previous studies 22,23,26 and indicates that the capsules are suitable for use in general medical practice. Additionally, patients' preferences were unequivocally in favour of capsules.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In both groups, a majority of the patients achieved sufficient 25(OH)D values, and only 12% reached the optimal range. This result is in line with previous studies 22,23,26 and indicates that the capsules are suitable for use in general medical practice. Additionally, patients' preferences were unequivocally in favour of capsules.…”
Section: Discussionsupporting
confidence: 93%
“…Sample size was calculated according to the assumed difference in the mean 25(OH)D serum values between the patient groups with monthly intake of 24,000 IU cholecalciferol and the patient group with loading regimen. We assumed that 25(OH)D serum value reach 55 ± 18 nmol/l following a monthly treatment 22 , and 75 nmol/l following the loading regimen, which corresponds to a difference of 20 nmol/l. Thus, we need 37 patients (17 patients per group + 3 drop-outs) to detect whether the stated difference exists between the two means with a power of 90%, a significance level at 5%, and a drop-out rate of 10% 25 .…”
Section: Study Visits Laboratory Measurements and Questionnaires Serum Concentrations Of 25(oh)dmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Miao et al (2020), Jin et al (2020 detected significant reductions in TC and LDL-C in females with polycystic ovary syndrome who were administered with vitamin D supplements (Jin et al, 2020;Miao et al, 2020). We suggested that postmenopausal women with an apparently normal status of health might not need to be adherent to vitamin D prescription regimen, as patients tend to prefer monthly to weekly or to daily administrations of vitamin D supplements (Rothen et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Daily, weekly, or monthly vitamin D supplementation, at equivalent doses, lead to similar increases in 25(OH)D serum concentrations, when measured after 2 to 3 months [ 65 , 66 , 67 ]. Adherence may be better with intermittent vitamin D dosing, but there are also concerns that high intermittent vitamin D doses may be less beneficial or might even be harmful in certain settings [ 67 , 68 , 69 ]. In view of the available evidence from clinical vitamin D trials and some pathophysiological considerations (e.g., altered vitamin D metabolism with high intermittent vitamin D doses), a daily vitamin D dosing schedule should rather be preferred, but when exceedingly high intermittent vitamin D doses are avoided, a weekly or monthly dosing schedule can also be applied [ 66 , 67 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%